STRATEGI PENINGKATAN KINERJA KARYAWAN PADA PERUSAHAAN CV EIWA KOTA MAKASSAR - Ayu, Sri; Suwanti, Ratih (Universitas Ichsan Sidenreng Rappang, 2025)
Achieving the target determined by the company by looking at the level of the company's ability to meet market needs is the goal of a company in making a profit. but in fact the company so far based on the data obtained by the author has not been able to meet the employee performance targets set by the company. So that the company in its development has not been maximized. Based on these problems, the author in this study aims to analyze strategies for improving employee performance. The method used in this study is a qualitative descriptive method which explains the strategy for improving employee performance at CV Eiwa Makassar city. The data analysis technique used by the author in this study is a qualitative data analysis technique which is carried out through the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the strategy for improving employee performance at CV Eiwa Makassar city has not been carried out routinely. This is due to a lack of understanding of things that can improve employee performance and the company's level of concern that is still not optimal for the welfare of its employees. In addition, in terms of improving employee performance, the company has not been able to implement it according to employee needs due to financial and non-financial limitations.